A transgenic RNAi approach for developing tomato plants immune to Pepinomosaic virus. (3rd February 2021) - Leibman, Diana; Ortega‐Parra, Nelia; Wolf, Dalia; Shterkman, Meital; Hanssen, Inge; Gal‐On, Amit
Abstract: RNA interference (RNAi) or gene silencing is a natural defence response of plants to invading viruses. Here, we applied this approach against pepino mosaic virus (PepMV) isolates in their natural host, tomato. PepMV isolates differ in their genetic sequences, the severity of the disease they induce, and their worldwide distribution. PepMV causes heavy crop losses, mainly due to impaired tomato fruit quality. Resistant varieties are not yet available, despite many years of resistance breeding efforts within the tomato seed industry. To generate broad resistance to PepMV strains, conserved sequences from three different strains of PepMV (US1, LP, and CH2) were synthesized as a single insert and cloned in a hairpin configuration into a binary vector, which was used to transform tomato plants. Transgenic tomato lines that expressed a high level of transgene‐siRNA exhibited immunity to PepMV strains, including a new Israeli isolate. This immunity was maintained even after graft inoculation, in which a transgenic scion was grafted onto nontransgenic infected rootstocks. However, an immune transgenic rootstock was unable to induce resistance in a nontransformed scion. These results provide the first example of engineered immunity to diverse PepMV strains in transgenic tomato based on gene silencing. Abstract : Tomato with a high level of transgene‐siRNA in a hairpin configuration have immunity to diverse PepMV strains (EU‐a, LP‐m, US1‐a, CH2‐a, CH2‐m, CH2‐pvu, CH2‐IL), the first example of immunity to PepMV in tomato using gene silencing.